Clinical and laboratory characteristics and associated risk factors of infants hospitalized in neonatal unit due to indirect hyperbilirubinemia. Issue 1 (2012) - Tan, İlhan and Salihoğlu, Özgül and Demirelli, Yaşar and Hatipoğlu, Sami
No abstract available